Autoethnography and Assimilation: Composing Border Stories - Mark Noe (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Introducing autoethnography in composition classes brings together personal narratives, academic discourse, and awareness of audience in surprising ways among students in south Texas.